Paroxysmal Movement Disorder and Epilepsy Caused by a De Novo Truncating Mutation in KAT6A - Efthymiou, Stephanie; Salpietro, Vincenzo; Bettencourt, Conceicao; Houlden, Henry (Journal of Pediatric Genetics, 2018)
Mutations in KAT6A encoding a histone acetyltransferase involved in chromatin remodeling and in other genes involved in histone acetylation and/or deacetylation have been implicated in broad phenotypes of congenital and developmental abnormalities. However, limited genotype–phenotype correlations are available for some of the most rare or recently reported genetic disorders related to chromatin dysregulation. We hereby report a de novo truncating mutation in KAT6A (c.3338C > G; p.S1113X) in a young male patient with intellectual disability associated with impaired speech and autistic features, who also presented with infantile seizures and a complex movement disorder phenotype with paroxysmal episodes of abnormal startle responses.
Keywords: KAT6A; startle reflex syndrome; global developmental delay